MANAGEMENT OF INDUSTRY COOPERATION AND THE WORLD OF WORK (IDUKA) WITH SMKN 1 TAPAKTUAN CONCENTRATION OF EXPERTISE (TKJ) ON FIELD WORK PRACTICE EXPERIENCE - Ivan Suhendra; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Management of Industrial Cooperation and the World of Work (IDUKA)between SMK Negeri 1 Tapaktuan Concentration of Expertise (TKJ) andincreasing practical fieldwork experiences for students. IDUKA is acollaborative program that aims to facilitate opportunities for collaborationbetween schools and the industrial world to better prepare students to enter theworld of work. This article describes how Tapaktuan 1 Public VocationalSchool establishes partnerships with various companies in the technology andcomputer network sectors, providing opportunities for TKJ students to take partin apprenticeship programs or field work practices. The benefits of IDUKA andpractical work experience are significant, as students gain insight into industrialwork processes and opportunities to interact with experienced professionals, aswell as reduce the gap between the world of education and the world of work.Periodic evaluations are also recognized as important to ensure that the IDUKAprogram is always relevant to industry developments that are constantlychanging. This program is a clear example of how collaboration betweenschools and industry can improve the quality of education and student careerpreparation. Overall, this article concludes that the Management of IndustrialCooperation and the World of Work (IDUKA) between SMK Negeri 1Tapaktuan Concentration of Expertise (TKJ) provides great benefits forstudents in preparation for the world of work. This collaboration is a clearexample of how collaboration between schools and industry can improve thequality of education and student career preparation.